EFFECT OF PLANTING SYSTEMS AND AGE TO PRODUCE SOME VARIETY seedlings SAWAH RICE (Oryza sativa L.) - Efrida Lubis (AGRIUM: Jurnal Ilmu Pertanian, 2016)
"Effect of Cropping Systems and Production Against Some Age seedlings Rice Varieties (Oryza sativa L.). order to determine the optimal level of influence and treatment of the System (S), Variety (V), Age seedlings (U) and Interaction on rice production. Installation Experiments conducted at the Research and Technology Assessment of Agricultural Market Leaning, Highway Galang Km Deli Serdang, North Sumatra Province, May s / d August 2003. The draft Plots Plots Divided. Planting System (S) as the main plot consists of two systems, namely Legowo (S1) and Tegel (S2). Varieties Petak child is comprised 4 types of IR-64 (V1), Ciherang (V2), Singkil (V3) and Sunggal (V4). Children and Age seedling plots are composed of 4 levels, namely 12 days (U1), 15 days (U2), 18 days (U3) and 21 days (U4). The parameters observed, Total Malai per clumps, contains per Malai Total Grain, Grain percentage Empty per Malai, Weight Total Dry Grain Harvest, 1000 grain weight of Dry Grain Results showed that the highest number of panicles per hill on S1U3 (18.48 stalk) and V3U3 (19.00 stalk), Total grain contains the highest permalai on S1U3 (88.15 grains), the percentage of empty grain at least in S1V1U3 (9.07%), the total weight of dry grain harvested per plot highest S1V4U3 (21.93 kg), a dry weight of 1000 grains in S2V2U1 (30.17 g)